Alcohol consuming habits and its effect on adherence and blood glucose level in type 2 diabetes mellitus - Maskey, R (Health Renaissance, 2011)
DOI: http://dx.doi.org/10.3126/hren.v9i3.5595 HR 2011; 9(3): 215